Perception of farmers towards the effectiveness of extension activities by Department of Agriculture (DOA) in Merbok minor granary area - Muhd Zuki, Nurul Hazwani (2017)
Paddy farming in Malaysia is currently declining direction. Malaysia was at a unstable position for rice self-sufficiency level. Then, vigorous modernization and development of the country might cause paddy farming was seen as unlikely as a good option. Malaysia development was start focusing on the economic crops such as rubber and oil palm. In 2005, the rice self-sufficiency level was dropping to 65% and this percentage not changes much until recent years. Agricultural extension services are mainly responsible to create awareness among farming communities and to help uplift the living standards of rural people through educational procedures. However, they are many problems still facing by agriculture sector. Among the problems are farmers still practice conventional method farming. Beside, low participation in training given by DOA is one of the factors why technologies and development are not practicing by farmers. The other problems faces are lack communication between farmers and extension officers and that extension officers also have low in knowledge and technical in agriculture. Farmers also have problem in willingness to increase their production which is they are scared to invest capital such as using new fertilizer, using new method or machines to increase their production of paddy. The specific objectives of the study are to identify the respondents‟ profile and to determine respondents‟ perception levels towards agricultural extension activities and extension officers. Then, to investigate the relationship between socio demographic factors and respondents‟ perception level towards extension activities and extension officers. To determine the perception of farmers‟ towards the effectiveness of extension activities by Department of Agriculture (DOA), minor granary area Merbok in Kedah was selected. This area was selected due to the potential of area as paddy production area which supports major granary area production if the farmers increase their productivity. The questionnaires were distributed to 150 respondents among paddy farmers. They are being interview via structured questionnaire to determine the socio demographic profile, farm profile, perception toward knowledge, skills, attitude and practices, perception towards agriculture agency and extension activities, perception towards agriculture agency, agriculture officer and extension activity and others. All the data collected were in a raw form and statistical analysis with SPSS version 24.0 software was carried out to analyse these data. For descriptive analysis, perception of farmers towards agriculture agency, agriculture officers and extension activities are classified as low. For chi-square results, perception of farmers towards knowledge, skills, attitude and practices and perception of farmers towards agriculture agency and extension activities were classified as high perception level. For regression analysis result, the largest contribution to dependent variable is education in agriculture (b=0.254). Overall, out of the three social demographic variables, education in agriculture is the only variables to have significant impact on dependent variable. The socio demographic variables do not have significant relationship with farmers‟ perception on agriculture officers and perception on agriculture activities respectively. As an overall conclusion, research crucial to be concern in the future study is a specific idea need to be make up and voice out to overcome the presence problem of lack of extension activities and role of agriculture officer in this area. Agriculture agency play an important roles to assist farmer in manage their paddy farming. Some respondents agree that agriculture agency is not uniform give the assistance to farmer. Farmers should make a complaint about this issues is a way to overcome this problem. Most farmers are depending to agriculture agency in order to guide them to be a successful farmer.